Moralitas Humanis dalam Hukum Pidana Indonesia: Analisis Pasal 463 KUHP Baru tentang Aborsi Korban Peekosaan Berbasis Formula Radbruch - Mohamad Deden Mutakin (Journal of Global Legal Review, 2025)
The policy of criminalizing abortion often causes moral tension between protecting the right to life of the fetus and protecting the humanity of rape victims. Therefore, the presence of Article 463 paragraph (2) of the New Criminal Code (KUHP), which exempts rape victims from criminal punishment, is crucial to examine, in order to observe the shift in Indonesia's criminal law paradigm from rigid positivism toward a more humanistic and just approach. This study analyzes Indonesia's criminal law response to the moral dilemma of protecting victims (humanity) and protecting life (the fetus), to the moral dilemma of protecting victims (humanity) and protecting life (the fetus), focusing on the extent to which this exemption from criminal abortion reflects a fundamental shift towards a more humanistic and just legal morality (Substantive Justice). This study uses a literature review method, which uses credible books and journals as references. This study aims to explore the article in responding to and accommodating the protection of fetuses and victims, as well as how the reciprocal relationship between law and morality is implemented in Indonesia's new criminal justice system. The results of the study show that: 1) Article 463 paragraph (2) of the New Criminal Code accommodates the demands of human morality by explicitly excluding criminal liability for female victims of rape or other sexual violence that results in pregnancy, provided that the pregnancy is no more than 14 (fourteen) weeks old or there are indications of a medical emergency; 2) This exemption is a progressive response that explicitly recognizes the physical and psychological trauma experienced by victims, placing the protection of victims' human rights and dignity as a primary consideration in the enforcement of criminal law; 3) This exception reflects a fundamental shift from rigid and positivistic legal morality (which previously punished all forms of abortion) towards a more humanistic and fair legal morality (Substantive Justice); 4) This shift is evident in the recognition of the status of the victim as a factor that negates the material unlawfulness of the act of abortion, and in a context-based approach that prioritizes substantive justice for the most vulnerable individuals; and 5) Thus, the New Criminal Code moves beyond formal procedural justice towards justice that takes into account the existential conditions and trauma of the victim.